New onset of Bell’s palsy in a patient with West Nile Encephalitis - Tetyana Vaysman (Clinical Case Reports, 2020)
Abstract The case report presented a patient who was diagnosed with West Nile virus encephalitis and developed new onset of Bell's palsy within 8 days of diagnosis. Given the incidence of WNV, it would be beneficial to evaluate WNV‐infected patients for peripheral neuropathy which nowadays has quite practical implication.